PENERAPAN METODE DIRECTED READING ACTIVITY (DRA) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PADA MATAKULIAH KOMUNIKASI PEMERINTAHAN DI PRODI ILMU PEMERINTAHAN UIN STS JAMBI - Suryawahyuni Latief; YULFI ALFIKRI NOER (Jurnal Literasiologi, 2020)
The major purpose of this study is to improve the critical thinking of undergraduate student in a government communication field, UIN STS Jambi. The subject of this study was undergraduate students in semester VA in academic 2018/2019. The instruments used in this study was the last report of student results, observation paper, and a text reading with a title "hoax, de vide et impera millenial" with three questions: Q1 What does the topic about?, Q2 How do you manage the phenomenon? And Q3 How do you think about the text’s contents?. This study employs action research with two stages from October to December 2018. The result indicates that DRA methods is able to improve the critical thinking of undergraduates students.